Dynamics of GLP-1R peptide agonist engagement are correlated with kinetics of G protein activation - Giuseppe Deganutti; Yi-Lynn Liang; Xin Zhang; Maryam Khoshouei; Lachlan Clydesdale; Matthew J. Belousoff; Hari Venugopal; Tin T. Truong; Alisa Glukhova; Andrew N. Keller; Karen J. Gregory; Katie Leach; et al. (Nature Communications, 2022)
The glucagon-like peptide-1 receptor (GLP-1R) can be targeted in the treatment of diabetes, obesity and other metabolic disorders. Here, the authors assess the molecular mechanisms of peptide agonists binding to GLP-1R and the responses elucidated by these ligands, including distinct kinetics of G protein activation.